Magic and Misdirection: The Influence of Social Cues on the Allocation of Visual Attention While Watching a Cups-and-Balls Routine - Hergovich, Andreas; Oberfichtner, Bernhard (Frontiers in Psychology, 2016)
In recent years, a body of research that regards the scientific study of magic performances as a promising method of investigating psychological phenomena in an ecologically valid setting has emerged. Seemingly contradictory findings concerning the ability of social cues to strengthen a magic trick’s effectiveness have been published. In this experiment, an effort was made to disentangle the unique influence of different social and physical triggers of attentional misdirection on observers’ overt and covert attention. The ability of 120 participants to detect the mechanism of a cups-and-balls trick was assessed, and their visual fixations were recorded using an eye-tracker while they were watching the routine. All the investigated techniques of misdirection, including sole usage of social cues, were shown to increase the probability of missing the trick mechanism. Depending on the technique of misdirection used, very different gaze patterns were observed. A combination of social and physical techniques of misdirection influenced participants’ overt attention most effectively.